News shocks in the data: Olympic Games and their macroeconomic effects - Reply - Viktoria C. E. Langer; Wolfgang Maennig; Felix J. Richter (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2015)
Recent analyses relate increases in the growth rate of countries to anticipation effects caused by bidding for the Olympic Games, so called news shocks. We argue that these findings should be interpreted cautiously. First, these analyses may suffer from an omitted variable bias because they neglect key determinants of economic growth. Second, these analyses compare the bidders for the Olympic Games to all other countries in the world, which constitutes a comparison between groups that show large differences in their structural characteristics. We show that including established determinants of economic growth and comparing the bidders to a suitable control group may lead to a complete disappearance of the anticipated economic effects of Olympic Games.
Keywords: E62; E65; F1; L83; 330; Anticipated shock; Olympic Games; GDP growth; matching; mega event